The Effect of Work Discipline and Compensation on Employee Productivity (A Study at PT. Tani Tangkas Makmur, Palopo City) - Salim, Ali Wahyu Asshiddiq; Saharuddin, S.; Patra, I Ketut (Manunggal Halim Jaya, 2026)
Study the quantitative discipline of work and compensation to productivity Among Employees at PT. Tani Tangkas Makmur, Palopo City . Using a saturated sampling technique, data were collected through a questionnaire from 55 respondents and analyzed with SPSS version 25. The results show that, to some extent, good discipline, Work, and compensation are influential and have a significant positive effect on productivity. Simultaneously, they also have a significant positive influence. Implications study. This upholds the importance of improving discipline. Work through the implementation of proper policies and procedures, as well as giving adequate compensation in accordance with employee performance.